The Color Purple and Namaku Hiroko: Comparative Literature on Gender Inequality Issues - Rizkia Shafarini; Agry Pramita (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2022)
This research aims to compare and contrast the gender inequality concerns in Alice Walker's